Nitrogen-doped artificial graphite negative electrode material and preparation method and application thereof
By combining and calcining artificial graphite and nitrogen sources under alkaline conditions, introducing nitrogen elements and changing the molecular structure of graphite, the problem of insufficient circulation performance and capacity of artificial graphite anode materials in lithium-ion batteries is solved, and higher battery capacity is achieved and cycle life.
Patent Information
- Application Number
- CN202411504329.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The circulation performance and capacity of existing artificial graphite anode materials in lithium-ion batteries have not met expectations, and there are constraints on structural stability and electrochemical properties.
By recombining artificial graphite with nitrogen source under alkaline conditions and calcining, nitrogen elements are introduced, the molecular structure of the ink sheet is changed, and the connection between layers is enhanced.
It improves the capacity and cycle life of lithium-ion batteries and enhances the electrochemical performance of the negative electrode material.
Smart Images

Figure CN119461355A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of graphite negative electrode materials, and in particular relates to a nitrogen-doped graphite negative electrode material and a preparation method and application thereof. Background Art
[0002] As fossil fuel resources are increasingly depleted and accompanied by serious environmental pollution problems caused by their use, the country is vigorously supporting and developing new energy industries out of considerations such as cherishing resources and protecting the environment. Among them, lithium battery energy storage is one of the fastest-growing industries at present. Graphite negative electrode, as a key material that determines the rate performance and cycle life of lithium-ion batteries, has naturally attracted widespread attention.
[0003] Among them, artificial graphite as a negative electrode material for lithium-ion batteries shows excellent cycle performance and safety performance, making its output account for more than 60%, and the preparation process of artificial graphite is mature and the price advantage is obvious. It is the current mainstream negative electrode material. However, in practical applications, after the artificial graphite material used in the energy storage field is made into lithium-ion batteries, the battery cycle performance does not achieve the expected effect, and the battery capacity needs to be further improved. In the lithium-ion energy storage battery system, the key to determining the battery cycle life is the negative electrode. Therefore, when the negative electrode is constructed with artificial graphite material, the electrochemical properties of the artificial graphite material are particularly important. However, considering that some technical indicators of artificial graphite negative electrode materials are mutually restrictive, the preparation of artificial graphite negative electrode materials with excellent comprehensive performance has become an urgent problem to be solved in the development of lithium-ion batteries. Summary of the invention
[0004] In order to solve the technical problems existing in the background technology, the present application discloses a nitrogen-doped graphite negative electrode material and its preparation method and application. The nitrogen element is introduced by compounding and calcining artificial graphite with a nitrogen source under alkaline conditions, thereby changing the molecular structure of the ink flakes in the obtained negative electrode material and enhancing the connection between the layers, ultimately improving the capacity and cycle life of the obtained lithium-ion battery.
[0005] The present invention provides a nitrogen-doped artificial graphite negative electrode material, comprising the following steps:
[0006] S1, graphitizing the raw material coke to obtain artificial graphite;
[0007] S2. Compounding the artificial graphite with a nitrogen source under alkaline conditions and calcining the composite to obtain the negative electrode material.
[0008] In the present invention, the raw coke is graphitized to obtain artificial graphite with a regular structure. After the artificial graphite is compounded and calcined with a nitrogen source under alkaline conditions, the nitrogen element can be introduced into the graphite, changing the molecular structure of the graphite sheet and enhancing the connection between the layers. Since the graphitization temperature is relatively high, the nitrogen element is doped after the raw coke is graphitized to prepare the artificial graphite, which can avoid the loss of the nitrogen element caused by the high temperature conditions of graphitization.
[0009] Preferably, in step S1, the raw coke is at least one of needle coke, sponge coke or petroleum coke.
[0010] In the present invention, when raw coke is used as the main carbon source, needle coke, sponge coke or petroleum coke has a high carbon content and few impurities, and is very suitable for preparing artificial graphite.
[0011] Preferably, in step S1, before graphitizing the raw coke, the process further comprises: granulating the raw coke and a binder;
[0012] Preferably, the binder is at least one of petroleum asphalt, natural asphalt or coal asphalt;
[0013] Preferably, the amount of the binder is 8-12% of the mass of the raw coke.
[0014] In the present invention, asphalt is both a carbon source and a binder. When exposed to high temperature, the asphalt softens and begins to flow, allowing the asphalt to better wrap the raw coke particles.
[0015] In the present invention, when the amount of the adhesive accounts for 8-12% of the mass of the raw coke, the adhesive can just effectively bond the raw coke together.
[0016] Preferably, in step S1, the graphitization temperature is 2800-3200°C;
[0017] Preferably, the D50 particle size of the artificial graphite is 15-17 μm.
[0018] In the present invention, graphitization is to rearrange the carbon atoms in the mixture of raw coke and asphalt at high temperature to form a regular graphite crystal structure; among them, the artificial graphite with a particle size of 15-17μm has a relatively stable structure and can better withstand the volume changes caused by the insertion and extraction of lithium ions, which is beneficial to extending the cycle life of the battery.
[0019] Preferably, in step S2, the nitrogen source is at least one of polyvinyl pyrrolidone or 2-methylimidazole.
[0020] Preferably, in step S2, the compounding specifically comprises: mixing the artificial graphite, the nitrogen source and the alkaline solution into a paste;
[0021] Preferably, the pH of the alkaline solution is 9-10, preferably KOH or NaOH solution.
[0022] In the present invention, compared with the previous nitrogen doping, in which the artificial graphite is directly compounded and calcined with the nitrogen source, the artificial graphite and the nitrogen source are compounded and calcined under alkaline conditions, which can more effectively change the molecular structure of the ink sheet and enhance the connection between the layers:
[0023] This is because inorganic alkali causes artificial graphite to produce voids at high temperatures, and these voids make it easier for nitrogen sources to enter the interior of the graphite for doping, thereby changing the structure of the ink sheet molecules; therefore, the nitrogen doping described in the present invention not only occurs on the surface of the graphite, but also penetrates deep into the ink sheet molecules. The nitrogen atoms doped inside and outside the graphite and the graphite itself form a conductive network, and the existence of the conductive network enhances the connection between the layers, thereby effectively reducing the damage to the graphite structure during the insertion and extraction process of lithium ions.
[0024] Preferably, in step S2, before the compounding, the step further includes: subjecting the artificial graphite to a substitution condensation reaction with chloroacetic acid to obtain carboxylated artificial graphite.
[0025] In the present invention, the artificial graphite is substituted with chloroacetic acid to form artificial graphite with carboxyl groups on the surface, thereby increasing the surface polarity of the artificial graphite. When it is subsequently compounded with a nitrogen source such as polyvinyl pyrrolidone or 2-methylimidazole, an effective hydrogen bond adsorption effect can be formed on the two, thereby promoting the effective coating of polyvinyl pyrrolidone or 2-methylimidazole on the surface of the artificial graphite, facilitating the calcination of the latter to form a tightly bonded nitrogen-doped carbon shell layer, and further improving the electrochemical performance of the negative electrode material.
[0026] Preferably, in step S2, the calcination temperature is 700-900°C;
[0027] Preferably, the calcination is carried out under inert gas conditions.
[0028] In the present invention, the calcination temperature of 700-900° C. satisfies the requirements of nitrogen doping and carbonization of the nitrogen source, while the inert atmosphere is to avoid oxidation.
[0029] The present invention also provides a nitrogen-doped artificial graphite negative electrode material, which is obtained by the above preparation method.
[0030] The present invention also provides a lithium-ion battery, which comprises the above-mentioned nitrogen-doped artificial graphite negative electrode material.
[0031] Beneficial effects of the present invention:
[0032] (1) By nitrogen doping artificial graphite, the discharge specific capacity of a lithium ion battery containing the artificial graphite negative electrode material is increased.
[0033] (2) Nitrogen is introduced through a unique doping method to change the molecular structure of artificial graphite sheets, enhance the connection between layers, and ultimately improve the capacity and cycle life of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a 500-fold scanning electron microscope image of the nitrogen-doped artificial graphite negative electrode material prepared in Example 1;
[0035] Figure 2 This is a 3000x scanning electron microscope image of the nitrogen-doped artificial graphite negative electrode material prepared in Example 1. DETAILED DESCRIPTION
[0036] Example 1
[0037] This embodiment provides a nitrogen-doped artificial graphite negative electrode material, and the specific method includes the following steps:
[0038] (1) Sample A was obtained by crushing and grinding petroleum coke (volatile matter ≤ 15%), and the D50 of sample A was 10.21 μm; coal tar pitch (softening point of 150°C) was added to sample A, and the coal tar pitch addition ratio was 10 wt % of sample A, and sample B was obtained after granulation at 550°C, and the D50 of sample B was 19.60 μm; sample B was graphitized at 2950°C to obtain sample C, and the D50 of sample C was 16.47 μm;
[0039] (2) Sample C and PVP powder were mixed in a mass ratio of 5:1, and a pH=10 KOH solution of 3 times the mass of the PVP powder was added, and the mixture was stirred and mixed into a paste, and then calcined at 800° C. in a nitrogen atmosphere to obtain sample D;
[0040] (3) After washing sample D with deionized water, it was dried in an oven at 80° C. for 12 h. The dried sample was ground to obtain sample E, which is the nitrogen-doped artificial graphite negative electrode material.
[0041] The artificial graphite negative electrode material obtained in the above embodiment was tested by scanning electron microscope, and the results are shown in Figure 2. Figure 1 , 2 It can be seen that the nitrogen-doped artificial graphite negative electrode material described in the embodiment is a multi-fold layer structure.
[0042] Example 2
[0043] This embodiment provides a nitrogen-doped artificial graphite negative electrode material, and the specific method includes the following steps:
[0044] (1) Sample A was obtained by crushing and grinding petroleum coke (volatile matter ≤ 15%), and the D50 of sample A was 10.21 μm; coal tar pitch (softening point of 150°C) was added to sample A, and the coal tar pitch addition ratio was 10 wt % of sample A, and sample B was obtained after granulation at 550°C, and the D50 of sample B was 19.60 μm; sample B was graphitized at 2950°C to obtain sample C, and the D50 of sample C was 16.47 μm;
[0045] (2) Sample C and 2-methylimidazole were mixed in a mass ratio of 5:1, and a KOH solution with a pH value of 10 in an amount 3 times the mass of 2-methylimidazole was added, and the mixture was stirred and mixed to form a paste, and then calcined at 800° C. in a nitrogen atmosphere to obtain sample D;
[0046] (3) After washing sample D with deionized water, it was dried in an oven at 80° C. for 12 h. The dried sample was ground to obtain sample E, which is the nitrogen-doped artificial graphite negative electrode material.
[0047] Example 3
[0048] This embodiment provides a nitrogen-doped artificial graphite negative electrode material, and the specific method includes the following steps:
[0049] (1) Petroleum coke (volatile matter ≤ 15%) was crushed and ground to obtain sample A, and the D50 of sample A was 10.21 μm; coal tar pitch (softening point of 150°C) was added to sample A, and the coal tar pitch addition ratio was 8wt% of sample A, and granulated at a temperature of 650°C to obtain sample B, and the D50 of sample B was 18.79 μm; sample B was graphitized at 3200°C to obtain sample C, and the D50 of sample C was 15.84 μm;
[0050] (2) Sample C and PVP powder were mixed in a mass ratio of 10:1, and a pH=10 KOH solution was added in an amount 3 times the mass of the PVP powder. The mixture was stirred and mixed into a paste, and then calcined at 900° C. in a nitrogen atmosphere to obtain sample D;
[0051] (3) After washing sample D with deionized water, it was dried in an oven at 80° C. for 12 h. The dried sample was ground to obtain sample E, which is the nitrogen-doped artificial graphite negative electrode material.
[0052] Example 4
[0053] This embodiment provides a nitrogen-doped artificial graphite negative electrode material, and the specific method includes the following steps:
[0054] (1) Sample A is obtained by crushing and grinding petroleum coke (volatile matter ≤ 15%), and the D50 of sample A is 10.21 μm; coal tar pitch (softening point is 150°C) is added to sample A, and the coal tar pitch addition ratio is 12wt% of sample A, and sample B is obtained after granulation at 500°C, and the D50 of sample B is 20.32 μm; sample B is graphitized at 2800°C to obtain sample C, and the D50 of sample C is 17.51 μm;
[0055] (2) Sample C and PVP powder were mixed in a mass ratio of 10:3, and a pH=10 KOH solution of 3 times the mass of the PVP powder was added, and the mixture was stirred and mixed to form a paste, and then calcined at 700° C. in a nitrogen atmosphere to obtain sample D;
[0056] (3) After washing sample D with deionized water, it was dried in an oven at 80° C. for 12 h, and then the dried sample was ground to obtain sample E, which is the nitrogen-doped artificial graphite negative electrode material.
[0057] Example 5
[0058] This embodiment provides a nitrogen-doped artificial graphite negative electrode material, and the specific method includes the following steps:
[0059] (1) Sample A was obtained by crushing and grinding petroleum coke (volatile matter ≤ 15%), and the D50 of sample A was 10.21 μm; coal tar pitch (softening point of 150°C) was added to sample A, and the coal tar pitch addition ratio was 10 wt % of sample A, and sample B was obtained after granulation at 550°C, and the D50 of sample B was 19.60 μm; sample B was graphitized at 2950°C to obtain sample C, and the D50 of sample C was 16.47 μm;
[0060] (2) After adding sample C to water and uniformly dispersing it by ultrasonic, 10 wt% KOH and 5 wt% chloroacetic acid by weight of sample C were added, and after ultrasonic reaction at 60° C. for 6 h, the mixture was filtered and dried to obtain sample D; sample D and 2-methylimidazole were mixed at a mass ratio of 5:1, and a pH=10 KOH solution of 3 times the mass of 2-methylimidazole was added, the mixture was stirred and mixed to form a paste, and then the mixture was calcined at 800° C. in a nitrogen atmosphere to obtain sample E;
[0061] (3) After washing sample E with deionized water, the sample was dried in an oven at 80° C. for 12 h. The dried sample was ground to obtain sample F, which is the nitrogen-doped artificial graphite negative electrode material.
[0062] Comparative Example 1
[0063] This comparative example proposes an artificial graphite negative electrode material. The specific method refers to step (1) in Example 1. After obtaining sample C, it is the artificial graphite negative electrode material.
[0064] Comparative Example 2
[0065] This comparative example proposes an artificial graphite negative electrode material, and the specific method includes the following steps:
[0066] (1) Crushing and grinding petroleum coke (volatile matter ≤ 15%) to obtain sample A, the D50 of sample A is 10.21 μm; coal tar pitch (softening point is 150°C) and PVP powder are added to sample A and mixed evenly, the coal tar pitch addition ratio is 10wt% of sample A, and the PVP powder addition ratio is 20wt% of sample A; granulation is performed at 550°C to obtain sample B, the D50 of sample B is 22.25 μm; sample B is graphitized at 2950°C to obtain sample C, the D50 of sample C is 18.24 μm;
[0067] (2) After washing sample C with deionized water, it was dried in an oven at 80° C. for 12 h, and then the dried sample was ground to obtain sample D, which is the artificial graphite negative electrode material.
[0068] Comparative Example 3
[0069] This comparative example proposes an artificial graphite negative electrode material. The specific method is similar to that of Example 1, except that in step (2), after sample C and PVP powder are mixed in a mass ratio of 5:1, water 3 times the mass of the PVP powder is added, the mixture is stirred and mixed into a paste, and then calcined at 800°C in a nitrogen atmosphere to obtain sample D.
[0070] The particle size, tap density, specific surface area and degree of graphitization of the artificial graphite materials obtained in the above examples and comparative examples were tested:
[0071] When testing the particle size, the artificial graphite material is dispersed in ethanol using ultrasonic vibration, and then the dispersed sample is placed in the sample cell of the Malvern 3000 laser particle size analyzer, and the instrument is started for measurement;
[0072] During the tap density test, the artificial graphite negative electrode material is poured into the sample tube of the tap density meter. After tapping at a vibration frequency of 200 times / minute, a vibration amplitude of 8mm, and a tap time of 20 minutes, a caliper is used to measure the height h of the sample in the sample tube, and the inner diameter r of the sample tube is recorded. The tap density is calculated according to the density formula, ρ=m / πr 2 h;
[0073] The specific surface area test was carried out by using the gas adsorption BET method, and the ASAP3020 specific surface area and pore size analyzer from Micromeritics was used for the test;
[0074] The graphitization degree is tested by using an X-ray powder diffractometer (model: Shimadzu XRD-7000), with a Cu (copper) target, an X-ray tube voltage of 35 kV, a current of 35 mA, a scanning angle range of (2θ) 5°-90°, a scanning step of 0.01°, and a time of 2 s per step. At the same time, silicon powder accounting for 15% of the mass of the artificial graphite material is added. According to the principle of the internal standard method, the peak position of the silicon standard is used to calibrate the instrument and the test error, so as to accurately calculate the characteristic peak position of the negative electrode material and obtain the graphitization degree.
[0075] Table 1 Physical property test results of the artificial graphite negative electrode materials described in the embodiments and comparative examples
[0076]
[0077] The electrochemical properties of the artificial graphite materials obtained in the above examples and comparative examples were tested:
[0078] The artificial graphite negative electrode material, conductive agent (acetylene black), binder (polyvinylidene fluoride, PVDF) and solvent (N-methylpyrrolidone, NMP) described in the above embodiment or comparative example are stirred to form a slurry, wherein the mass ratio of the artificial graphite negative electrode material, acetylene black and polyvinylidene fluoride is 8:1:1; the slurry is coated on a copper foil current collector, and then dried to remove the solvent, and then rolled to obtain a negative electrode sheet;
[0079] The above-mentioned negative electrode sheet is used as the working electrode, the metal lithium sheet is used as the counter electrode, and a diaphragm (polypropylene diaphragm) and an electrolyte are used for assembly in a glove box, wherein the electrolyte is a 1 mol / L LiPF6 solution, the solvent is DMC+EMC+EC=1:1:1, and the mass ratio of the electrolyte to the negative electrode sheet is 4:1; during assembly, the environment is ensured to be dry and oxygen-free to obtain a lithium-ion battery; a battery testing system is used to perform a constant current charge and discharge test on the assembled lithium-ion battery, and different charge and discharge current densities and voltage ranges are set to obtain important parameters such as the first charge and discharge capacity, coulomb efficiency, and cycle performance (the number of cycles to decay to 80% of the initial capacity) of the artificial graphite negative electrode material described in the embodiment or comparative example, and the results are shown in Table 2 below:
[0080] Table 2 Electrochemical performance test results of the artificial graphite negative electrode materials described in the examples and comparative examples
[0081] First discharge specific capacity (mAh / g) First efficiency (%) Cycle times (times) Example 1 348.5 94.3 4216 Example 2 349.2 94.4 4279 Example 3 347.8 93.9 4130 Example 4 347.2 93.8 4025 Example 5 351.6 94.0 4451 Comparative Example 1 344.4 93.0 3453 Comparative Example 2 345.6 93.3 3612 Comparative Example 3 346.7 93.5 3551
[0082] The theoretical discharge capacity of graphite is 372 mAh g-1 Therefore, it is quite difficult for those skilled in the art to further improve the discharge capacity of graphite based on the existing technology. From the data of Comparative Example 1 and Example 1 in Table 2, it can be seen that Example 2 increases the discharge capacity of graphite from 344.4 mAh·g to 1.5 mAh·g by nitrogen doping alone. -1 Increased to 348.5mAh g -1 , this improvement is a great technological advancement in this field.
[0083] Longer cycle times are also an urgent problem that needs to be solved in battery development. In existing technologies, nitrogen doping is usually used to improve the electrochemical performance of batteries, but there are few reports on the technology of significantly improving the cycle capacity of artificial graphite by only nitrogen doping.
[0084] It can be seen from the data in Table 2 that, compared with Example 1, when the non-nitrogen-doped artificial graphite negative electrode material prepared in Comparative Example 1 is applied to a lithium-ion battery, various chemical properties, especially the number of cycles, are greatly reduced.
[0085] Compared with Example 1, the order of adding the nitrogen source in Comparative Example 2 is changed, and the nitrogen source is added before graphitization; since the temperature of graphitization is as high as 3000°C, nitrogen will be lost in large quantities at high temperature, so only a small amount of nitrogen is retained in the artificial graphite material obtained in Comparative Example 2. When this graphite material is applied to lithium-ion batteries, the electrochemical properties exhibited are inferior to those of Example 1.
[0086] Compared with Example 1, the artificial graphite in Comparative Example 3 is calcined without being compounded with the nitrogen source under alkaline conditions; although the nitrogen doping content of the artificial graphite material in Comparative Example 3 is not much different from that in Example 1, since most of the nitrogen elements are not doped into the interior of the artificial graphite, but are concentrated on the surface of the graphite, when lithium ions are embedded and extracted, the stress generated by the volume change is also concentrated on the surface of the graphite, causing the structure of the artificial graphite material to be destroyed. Ultimately, when the artificial graphite material of Comparative Example 3 is applied to a lithium-ion battery, the discharge specific capacity, initial efficiency and cycle performance are all worse than those of Example 1.
[0087] In summary, in the present invention, through a unique doping method, the nitrogen atoms doped inside and outside the graphite form a conductive network with the graphite itself, which effectively reduces the damage to the graphite structure during the insertion and extraction of lithium ions, thereby improving the cycle performance of lithium-ion batteries.
[0088] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a nitrogen-doped artificial graphite negative electrode material, characterized in that: The steps include: S1, graphitizing the raw material coke to obtain artificial graphite; S2. Compounding the artificial graphite with a nitrogen source under alkaline conditions and calcining the composite to obtain the negative electrode material.
2. The method for preparing the nitrogen-doped artificial graphite negative electrode material according to claim 1, characterized in that: In step S1, the raw coke is at least one of needle coke, sponge coke or petroleum coke.
3. The method for preparing the nitrogen-doped artificial graphite negative electrode material according to claim 1 or 2, characterized in that: In step S1, before graphitizing the raw coke, the process further includes: granulating the raw coke and a binder; Preferably, the binder is at least one of petroleum asphalt, natural asphalt or coal asphalt; Preferably, the amount of the binder is 8-12% of the mass of the raw coke.
4. The method for preparing the nitrogen-doped artificial graphite negative electrode material according to any one of claims 1 to 3, characterized in that: In step S1, the graphitization temperature is 2800-3200°C; Preferably, the D50 particle size of the artificial graphite is 15-17 μm.
5. The method for preparing the nitrogen-doped artificial graphite negative electrode material according to any one of claims 1 to 4, characterized in that: In step S2, the nitrogen source is at least one of polyvinyl pyrrolidone or 2-methylimidazole.
6. The method for preparing the nitrogen-doped artificial graphite negative electrode material according to any one of claims 1 to 5, characterized in that: In step S2, the compounding specifically includes: mixing artificial graphite, nitrogen source and alkaline solution into a paste; Preferably, the pH of the alkaline solution is 9-10, preferably KOH or NaOH solution.
7. The method for preparing the nitrogen-doped artificial graphite negative electrode material according to any one of claims 1 to 6, characterized in that: In step S2, before the compounding, the method further includes: subjecting the artificial graphite to a substitution condensation reaction with chloroacetic acid to obtain carboxylated artificial graphite.
8. The method for preparing the nitrogen-doped artificial graphite negative electrode material according to any one of claims 1 to 7, characterized in that: In step S2, the calcination temperature is 700-900°C; Preferably, the calcination is carried out under inert gas conditions.
9. A nitrogen-doped artificial graphite negative electrode material, characterized in that: The invention is obtained by the preparation method according to any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: It includes the nitrogen-doped artificial graphite negative electrode material as described in claim 9.
Citation Information
Patent Citations
Preparation method of high-magnification artificial graphite negative electrode material
CN111584866A
Nitrogen-containing artificial graphite negative electrode material, preparation method and application thereof, and battery
CN114195144A
Artificial graphite negative electrode material and preparation method and application thereof
CN115893403A
Nitrogen-doped artificial graphite, preparation method of nitrogen-doped artificial graphite, negative plate and application of negative plate
CN117623298A
Nitrogen-doped modified artificial graphite, preparation method thereof and lithium ion battery
CN118515269A
Cited By
Graphite negative electrode material with excellent high-temperature performance and preparation method thereof
CN121698339A
Graphite negative electrode material with excellent high-temperature performance and preparation method thereof
CN121698339B